HYPERTENSION HEALTH EDUCATION AND HYPERTENSION EXERCISE TRAINING IN THE ELDERLY AT WISMA CEMPAKA UPT PSTW JEMBER - Rista Dwi Pratiwi; Intan Rahmawati; Resita Ovina Intiyaskanti; Nila Uli Saadah; Badrus Sholeh; Tantut Susanto (Journal of Health Community Service, 2023)
The elderly are at higher risk of developing various degenerative diseases. Hypertension is often called the "Silent Killer", which can unwittingly cause death due to complications without proper treatment. Therefore, hypertension health education is expected to increase knowledge of the elderly, and hypertension exercise training can help reduce complications. This community service program aims to increase the elderly's knowledge of hypertension and be able to apply the hypertension exercise method at Wisma Cempaka UPT PSTW Jember. The community service method uses a gerontic nursing care approach which includes various stages, namely an initial survey related to hypertension through blood pressure checks in the elderly, then carrying out hypertension counseling with counseling methods and interactive discussions, then continuing with training on how to apply hypertension exercise by students and a joint demonstration with the Wisma elderly. Cempaka UPT PSTW Jember. The results of this activity indicate an increase in knowledge among the elderly regarding hypertension from 42% to 75% at the end of the activity. The average decrease in elderly blood pressure is ten mmHg in systolic and five mmHg in diastole after exercise hypertension for three consecutive days. This proves the importance of health education and training in the form of hypertension exercise to be carried out continuously in controlling blood pressure and minimizing the risk of hypertension complications in the elderly. Therefore, monitoring of exercise training and sustainable hypertension health education is expected to be continued regularly to maintain the health of the elderly.